2017
DOI: 10.1038/srep40265
|View full text |Cite
|
Sign up to set email alerts
|

Unique local bone tissue characteristics in iliac crest bone biopsy from adolescent idiopathic scoliosis with severe spinal deformity

Abstract: Adolescent idiopathic scoliosis is a complex disease with unclear etiopathogenesis. Systemic and persistent low bone mineral density is an independent prognostic factor for curve progression. The fundamental question of how bone quality is affected in AIS remains controversy because there is lack of site-matched control for detailed analysis on bone-related parameters. In this case-control study, trabecular bone biopsies from iliac crest were collected intra-operatively from 28 severe AIS patients and 10 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Several pathways leading to RUNX2 activation, such as BMP, bFGF and IGF, were found to converge at the MAPK cascade 32,49,50 . Moreover, several recent studies demonstrated that there are positive correlations between low RUNX2 expression and BMD in AIS patients 51,52 . These studies are consistent with our results, suggesting that MAPK signalling plays a key role in bone formation and may be implicated in AIS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways leading to RUNX2 activation, such as BMP, bFGF and IGF, were found to converge at the MAPK cascade 32,49,50 . Moreover, several recent studies demonstrated that there are positive correlations between low RUNX2 expression and BMD in AIS patients 51,52 . These studies are consistent with our results, suggesting that MAPK signalling plays a key role in bone formation and may be implicated in AIS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study firstly revealed a causative relationship between aberrant microRNA-145À5p (miR-145) expression and abnormal osteocyte structure and function in AIS [20]. The miR-145 expression inhibited osteocyte dendritic formation and function by disturbing active b-catenin expression and its transcriptional activity [18]. We also reported negative correlation between plasma miR-145 and serum levels of bone metabolic markers [18].…”
Section: Introductionmentioning
confidence: 92%
“…The root cause of low bone mass in AIS is unclear. Bone histomorphometry studies on bone biopsies from surgical cases indicated abnormally higher bone turnover in AIS [18,19]. It is speculated that an abnormality of bone metabolism in AIS possibly results in the spine being more vulnerable to deformity.…”
Section: Introductionmentioning
confidence: 99%
“…A compromised mechanical competence alongside low BMD also increases fracture risk and can be an underlying cause of scoliosis. (65)(66)(67) Unfortunately, natural history BMD data of CS patients throughout early development is not available, to the best of our knowledge.…”
Section: Abnormal Vertebrae and Vbmd Variabilitymentioning
confidence: 99%